Global incidence of bronchopulmonary dysplasia among extremely preterm infants: a systematic literature review. (3rd June 2021) - Siffel, Csaba; Kistler, Kristin D.; Lewis, Juliana F. M.; Sarda, Sujata P.
Abstract: Background: Infants born extremely preterm (<28 weeks gestational age (GA)) face a high risk of neonatal mortality. Bronchopulmonary dysplasia (BPD) is the most common morbidity of prematurity. Objective: To evaluate the global incidence of BPD among infants born extremely preterm. Design: A systematic review of the literature was conducted in Embase and MEDLINE (via PubMed) using a prespecified search strategy for BPD and prematurity. Observational studies published in English between 16 May 2006 and 16 October 2017 reporting on the occurrence of BPD in infants born <28 weeks GA were included. Results: Literature searches yielded 103 eligible studies encompassing 37 publications from Europe, 38 publications from North America, two publications from Europe and North America, 19 publications from Asia, one publication from Asia and North America, six publications from Oceania, and zero publications from Africa or South America. The reported global incidence range of BPD was 10–89% (10–73% in Europe, 18–89% in North America, 18–82% in Asia, and 30–62% in Oceania). When only population-based observational studies that defined BPD as requiring supplemental oxygen at 36 weeks postmenstrual age were included, the global incidence range of BPD was 17–75%. The wide range of incidences reflected interstudy differences in GA (which was inversely related to BPD incidence), birthweight, and survival rates across populations and institutions. Conclusions: BPD is a common health morbidity occurring with extremely preterm birth. Further study of factors that impact incidence, aside from low GA, may help to elucidate modifiable risks.